Uprooting and Settling In: The Invisible Strength of Deficit Thinking (LEARNing Landscapes, 2014)
In our neoliberal context, the field of teacher education faces many challenges and tensions. One crucial challenge that arises deals with the tensions of deficit thinking. Regrettably, these tensions are often left unaddressed due to the demanding subjectbased curriculum learning approach in most Bachelor of Education programs. This paper1 examines why deficit thinking, particularly toward "inner-city students," is ethically problematic and inconsistent with creating true democratic education possibilities. This key question is addressed in this paper in four parts: (1) the connection between neoliberalism and public education, (2) the meaning and forms of deficit thinking with respect to teaching, (3) ethical implications of deficit thinking on students’ public school experiences, and (4) a call for a genuine democratic education in teacher education.
Keywords: teacher education; deficit thinking; democtratic education